High resolution crystal structures of the receptor-binding domain of Clostridium botulinum neurotoxin serotypes A and FA - Davies, Jonathan R.; Hackett, Gavin S.; Liu, Sai Man; Acharya, K. Ravi (PeerJ, 2018)
The binding specificity of botulinum neurotoxins (BoNTs) is primarily a consequence of their ability to bind to multiple receptors at the same time. BoNTs consist of three distinct domains, a metalloprotease light chain (LC), a translocation domain (HN) and a receptor-binding domain (HC). Here we report the crystal structure of HC/FA, complementing an existing structure through the modelling of a previously unresolved loop which is important for receptor-binding. Our HC/FA structure also contains a previously unidentified disulphide bond, which we have also observed in one of two crystal forms of HC/A1. This may have implications for receptor-binding and future recombinant toxin production.
Keywords: SV2; Crystal structure; Botulinum neurotoxin; Targeted secretion inhibitor; FA hybrid; Receptor binding domain